Legal Aspec Bioprospecting Conservation of Medicinal Plants in Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
The country of Indonesia is an archipelago, which has various types of plants. One of them is a medicinalplant. This plant has ingredients that can be used as a treatment. But by seeing the high population growthof Indonesia, the medicinal plants are threatened. This makes the need for an action that can maintainthe existence of these medicinal plants. Bioprospection conservation is an effort to preserve and developmedicinal plants so that their presence is not lost.